Unique Characteristics of Prepubertal Onset Systemic Lupus Erythematosus - R. Abdwani; E. Abdalla; I. Al-Zakwani (International Journal of Pediatrics)
Objectives. The aim of this study was to investigate the influence of age at disease onset on disease expression and outcomes of pediatric systemic lupus erythematosus SLE (pSLE). Methods. A total of 103 patients with pSLE from Sultan Qaboos University Hospital, Oman, were retrospectively studied. Epidemiological, clinical phenotype, disease severity, serology, treatment, and outcome were compared among the three groups using univariate statistical tests. Results. The mean disease duration of the cohort was 9.8 ± 4.7 years. The patients were divided into three groups: prepubertal onset (n=39) with mean age at diagnosis of 5.1 ± 2.0 years and pubertal disease onset (n=29) with mean age at diagnosis of 10.8 ± 1.0 years as well as postpubertal disease onset (n=35) group with mean age at diagnosis of 15.3 ± 1.6 years. The prepubertal pSLE cohort demonstrates unique characteristics with increased frequency of familial SLE (61%) of which 49% were from first-degree relatives. Similarly, this group had distinctive clinical features, which included increased renal disease in pubertal and postpubertal groups, respectively (51% vs 23% vs 20%; p=0.039). Prepubertal, similar to pubertal group, had a higher incidence of cutaneous manifestations than in the postpubertal group (74% vs 69% vs 46%; p=0.029). Laboratory features in prepubertal group were distinct with increased frequency of positive anti-cardiolipin antibodies (47%), anti-glycoprotein antibodies (42%), ANCA (62%), and low complement levels (97%) compared to pubertal and postpubertal group. The prepubertal group also has the lowest frequency of positive SSA antibodies (18%) and SSB antibodies (5.1%). The overall mean SLEDAI score in pSLE cohort was 15.6 ± 18.5. The mean SLEDAI scores among the groups showed no significance difference (p=0.110). The overall SLICC DI ≥1 was 36% with a mean damage score of 0.76 ± 1.38. No significant differences in damage index (SLICC DI ≥1) were noted among the groups. Conclusions. Distinct clinical features were identified in prepubertal onset pSLE population of Arab ethnicity. Given the high rate of consanguineous marriage and high frequency of familial SLE in this cohort, these manifestations could be explained by higher frequency of genetic factors that influence the disease pathogenesis.